Bacteriological assessment of oyster (Crasostrea iradale) from selected outlets or "Talabahan" - Miguel, Christy Hualde
Raw shell stocks and boiled oysters were collected from three selected sources, Calumpang, Iloilo City (Source A), Arevalo, Iloilo City (Source B), and Miagao, Iloilo (Source C).